Comparative transcriptome, physiological and biochemical analyses reveal response mechanism mediated by CBF4 and ICE2 in enhancing cold stress tolerance in Gossypium thurberi - Cai, Xiaoyan (AoB Plants, 2019)
Low temperature is one of the key environmental stresses that impair plant growth and significantly restricts the productivity and spatial distribution of crop plants. Gossypium thurberi, a wild diploid cotton species, has adapted to a wide range of temperatures and exhibits a better tolerance to chilling stress. Here, we compared phenotypes and physiochemical changes in G. thurberi under cold stress and found this species indeed showed better cold tolerance. Therefore, to understand the molecular mechanisms of the cold tolerance in G. thurberi, we compared transcription changes in leaves of G. thurberi under cold stress by high-throughput transcriptome sequencing. In total, 35 617 unigenes were identified in the whole-genome transcription profile, and 4226 differentially expressed genes (DEGs) were discovered in the leaves upon cold treatment. Gene Ontology (GO) classification analyses showed that the majority of DEGs belonged to categories of signal transduction, transcription factors (TFs) and carbohydrate transport and metabolism. The expression of several cold-responsive genes such as ICE1, CBF4, RAP2-7 and abscisic acid (ABA) biosynthesis genes involved in different signalling pathways were induced after G. thurberi seedlings were exposed to cold stress. Furthermore, cold sensitivity was increased in CBF4 and ICE2 virus-induced gene silencing (VIGS) plants, and high level of malondialdehyde (MDA) showed that the CBF4 and ICE2 silenced plants were under oxidative stress compared to their wild types, which relatively had higher levels of antioxidant enzyme activity, as evident by high levels of proline and superoxide dismutase (SOD) content. In conclusion, our findings reveal a new regulatory network of cold stress response in G. thurberi and broaden our understanding of the cold tolerance mechanism in cotton, which might accelerate functional genomics studies and genetic improvement for cold stress tolerance in cultivated cotton.